Cardio-Oncology Educational Program: National Survey as the First Step to Start - Kozhukhov, Sergey; Dovganych, Nataliia (Frontiers in Cardiovascular Medicine, 2021)
Aim: The collaboration of cardiologists, general practitioners (GPs), and oncologists is crucial in cancer patient management. We carried out a national-based survey—The Ukrainian National Survey (UkrNatSurv)—on behalf of the Cardio-Oncology (CO) Working Group (WG) of the Ukrainian Society of Cardiology to analyze the level of knowledge in cardio-oncology. Methods: A short questionnaire was presented to specialists involved in the management of cancer patients across the country. The questionnaire was made up of eight questions concerning referred cancer patient number, CV complications of cancer therapy, diagnostic methods to detect cardiotoxicity, and drugs used for its treatment. Results: A total of 426 questionnaires of medical specialists from different regions of Ukraine were collected and analyzed; the majority of respondents were cardiologists (190), followed by GPs (177), 40 oncologists (mainly chemotherapists and hematologists), other −19 (imaging specialists, neurologists, endocrinologists, etc.). All responders were equally involved in the management of cancer patients. However, less than half of the patients have been seen before the start of cancer therapy. GPs observe the majority of patients after the end of treatment. All doctors are sufficiently aware of cancer therapy-associated CV complications. However, the necessary diagnostic tools, mostly biomarkers, are not used widely by different specialists. The criteria for cardiotoxicity, in particular, the level of reduction of the left ventricular ejection fraction (LVEF) as a marker of LV dysfunction, are not clearly understood. The specific knowledge in the management of CV complications in cancer is required. Conclusion: UkrNatSurv is the first survey in Ukraine to investigate the awareness of CO care provided to cancer patients with CV diseases (CVD) or developed CV complications. Providing such surveys among doctors involved in CO is an excellent tool to investigate the knowledge gaps in clinical practice. Therefore, the primary task is to develop a national educational CO program.